Pre-analytical phase - Portuguese EQAS (PNAEQ) since 2007 to 2014 - Faria, Ana Paula (2015)
The National External Quality Assessment Program (PNAEQ) is included in the Department of Epidemiology of the National Health Institute Doutor Ricardo Jorge, Portugal. The main goal of PNAEQ is to promote, organize and coordinate EQA schemes in 7 areas: Clinical, POCT, Genetics, Pathology and Air, Food and Water Microbiology. In order to enlarge the EQA schemes available, it was established a collaboration protocol with the Finnish company Labquality Oy. Since 2007, PNAEQ provides a program on pre-analytical phase with a transversal evaluation of the laboratory testing process and not only the frequently surveyed analytical phase. In 2014, in collaboration with Labquality Oy, were launched 4 specific schemes in this area: phlebotomy and POCT units, blood gas analysis, clinical chemistry and microbiology. In international literature, several studies describe preanalytical phase as more prone to errors due to the manually intensive activities like collection, handling, transportation, preparation and storage of specimens. Implementing quality indicators for preanalytical phase allow the laboratories to improve the services quality and patient safety.